Pengaruh Komsumsi Kripik Singkong Ebi Terhadap Tekanan Darah Pada Ibu Hamil Hipertensi Kabupaten Maros Tahun 2020 - Arfiani; Andi Nurlinda; Fairus Prihatin Idris (Journal of Muslim Community Health, 2020)
Introduction: The Maternal Mortality Rate (MMR) is a serious global health problem. DataWHO states that 585,000 mothers die during pregnancy or childbirth and more than half (58.1%) are due to hypertension. One of the causes of hypertension is lack of nutritional intake in the fulfillment of pregnant women. The purpose of this study was to analyze the effect of cassava chips consumption on blood pressure in hypertensive pregnant women at Cenrana Public Health Center, Maros Regency 2020. Method: using (Experiment Research) with a (true experimental) design. Subject characteristics in this study were pregnant women with hypertension. as many as 30 respondents, 15 in the intervention group and 15 in the control group with the proposive sampling technique. The statistical test in this study used the paired t test. Results : of the paired t test with the results of the effect and mean on systolic blood pressure with a mean value of 125,333 devatiaon standard 5,164 with a value of p 0,001, diastolic blood pressure mean 78,667, devatiaon standard 5,164 with a value p 0,001 while the protein kdar mean value 1.533 devatiaon standard 0.516 with a value p0.008. There is an effect of the consumption of cassava ebi chips on blood pressure in hypertensive pregnant women at the Cenrana Health Center and the Tompobulu Community Health Center, Maros Regency 2020. Suggestion: for health workers to further improve in providing counseling, especially for pregnant women about the benefits and nutritional content of Singong ebi chips as a distilled food that can be used to control blood pressure.